2012
DOI: 10.1200/jco.2012.42.4887
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Immuno–Positron Emission Tomography: Antibodies for Molecular Imaging in Oncology

Abstract: Identification of cancer cell-surface biomarkers and advances in antibody engineering have led to a sharp increase in the development of therapeutic antibodies. These same advances have led to a new generation of radiolabeled antibodies and antibody fragments that can be used as cancer-specific imaging agents, allowing quantitative imaging of cell-surface protein expression in vivo. Immunopositron emission tomography (immunoPET) imaging with intact antibodies has shown success clinically in diagnosing and stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
141
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(145 citation statements)
references
References 100 publications
2
141
0
2
Order By: Relevance
“…2 and 4; Table 1). Our results are consistent with those published by Wu and colleagues, who showed the advantages of using antibodies in mini-antibody format (functionally equivalent to SIP) and 124 I as a PET radionuclide (44,45).…”
Section: Discussionsupporting
confidence: 83%
“…2 and 4; Table 1). Our results are consistent with those published by Wu and colleagues, who showed the advantages of using antibodies in mini-antibody format (functionally equivalent to SIP) and 124 I as a PET radionuclide (44,45).…”
Section: Discussionsupporting
confidence: 83%
“…In our study, OR51E1 has shown more extensive membrane localization compared with SSTR2, SSTR3, and SSTR5, which are targeted by most of the clinically available SSAs. These findings indicated that OR51E1 might display a higher uptake in LC cells, compared with the SSA-based diagnostics, after developing appropriate procedures of immuno-positron emission tomography (PET; Knowles & Wu 2012) by means of OR51E1 monoclonal antibodies with high receptor binding affinity. Indeed, OR51E1 has shown an advantage over SSTRs as it has prevalence across the entire spectrum of LCs, even in OctreoScan-negative and/or SSTR non-IR LCs, independent of tumor size.…”
Section: Discussionmentioning
confidence: 98%
“…S3A). Particularly remarkable was the much higher tracer uptake liver [an organ exhibiting relatively high unspecific activity because of high blood perfusion, antibody metabolism, and potential transchelation of 64 Cu (28,36)]. The tumor-to-contralateral background, tumor-to-blood pool, and tumor-to-liver contrasts were 21.4 ± 8.2, 2.7 ± 0.9, and 2.6 ± 0.8 at 24 h and 32.8 ± 19, 6.4 ± 2.5, and 5.4 ± 1.8 at 48 h p.i., respectively.…”
Section: Resultsmentioning
confidence: 99%